PERATURAN TATA RUANG DALAM MEMBERIKAN IZIN MENDIRIKAN BANGUNAN PADA RUMAH IBADAH - Theresia Simanullang, Berty; Tobing, Maria; Helmi, Helmi (Mendapo: Journal of Administrative Law, 2021)
The Indonesian state is obliged to facilitate the people living within its territory so that they can live harmoniously side by side. Pancasila as the basis of the state strives to create harmony in the population including harmony in religion. Pancasila has been agreed to be the basis of the state and functions to protect religious plurality in Indonesia, one of which is in establishing houses of worship as stated in the 1945 Constitution Article 29 paragraph (2) which reads: "The state guarantees the independence of every citizen to embrace their respective religions and to worship according to that religion and belief â€. Therefore, houses of worship and the implementation of religious worship are important and fundamental matters for every religious community guaranteed by the state. But in reality, there are still many houses of worship that are not built in accordance with existing regulations in Indonesia, causing many conflicts and conflicts in the community.